Designing an Efficient Numerical Method for Solving the Blood Ethanol Concentration System and Ebola Virus Models (European Journal of Pure and Applied Mathematics, 2024)
This study aims to provide a numerical simulation of two important models called the Blood Ethanol Concentration (BEC) model and the Ebola Virus model in their fractional form (Caputo-Fabrizio sense (CF)). Here, we used Simpson’s 1/3 rule as an efficient numerical scheme for integration to solve the obtained fractional integral equations (FIEs) and reduce it to a collection of algebraic equations. Particular emphasis is placed on elucidating the error analysis of the given scheme. The results acquired by implementing the Runge-Kutta method (RK4M) and others are compared to the achieved results. The results explain that the implemented scheme offers a straightforward and effective tool for simulating solutions of these models. The primary benefit of the implemented method is that it relies on a small number of uncomplicated steps and does not have long-term effects. Finally, numerical simulations support the theoretical conclusions, showing the great agreement between the two.
Keywords: Blood ethanol concentration system; Ebola virus epidemic model; RK4M; Numerical integration